Plasma cortisol and blood glucose milieu as an index of stress in buffaloes with uterine torsion - GHUMAN, S P S; SHARMA, R D; PRABHAKAR, S; NANDA, A S (The Indian Journal of Animal Reproduction, 2023)
Uterine torsion is a highly stressful reproductive disorder in buffaloes (Ghuman, 1995; Manju et al, 1985). However, the degree of stress inflicted due to rolling of the dam, employed to detort the uterus has not been evaluated. The dam responds to mild to intense physical stress by releasing glucocorticoids and catecholamins (Axelrod and Reisine, 1984), which may be related synergistically to glucose levels. The present study was therefore, planned to assess the intensity of stress due to number of rolings employed to detort the uterus, by taking into consideration the plasma cortisol and blood glucose milieu as the indices of stress.